A Note on the Fuzzy Leonardo Numbers - Elen Viviani Pereira Spreafico; Eudes Antonio Costa; Paula Maria Machado Cruz Catarino (Transactions on Fuzzy Sets and Systems)
In this work, we define a new sequence denominated by fuzzy Leonardo numbers. Some algebraic properties of this new sequence are studied and several identities are established. Moreover, the relations between the fuzzy Fibonacci and fuzzy Lucas numbers are explored, and several results are given. In addition, some sums involving fuzzy Leonardo numbers are provided.